Economic Theory and Practice in the Asian Setting, Volume 3: The Economics of Agriculture. Edited by Committee on Economics Teaching Material for Asian Universities. New Dehli: Wiley Eastern Limited. (The Pakistan Development Review, 1977)
This book is the product of the efforts of a group of teachers who felt the need to provide Asian students with empirical work on agriculture which applies economic theory to their own environment. The papers in the volume are organized into six topics on Agriculture: (a) Management decisions on small farms; (b) importance of technical know-how; (c) mechanization of agri¬culture; (d) relationship between farm-size and productivity; (e) impact of food aid; and (f) agricultural policies of Asian countries. The major theme of the papers is that land holdings in Asian Countries are usually very small.